Spun pile / Muhammad Faris Abdul Jalil - Abdul Jalil, Muhammad Faris (2014)
History Establishment PWD DE Hulu Perak, 33300 Gerik Perak. According to a study made by the Perak PWD Historical Research Committee in 1998, Hulu Perak PWD was founded in 1884 and known as the ' Public Works Department ' (PWD). Hulu Perak PWD includes three (3) sub-district of Gerik ,Lenggong and Pengkalan Hulu with an area of approximately 6,500 square miles and is bordered by Thailand, Kedah, Kelantan, Larut Matang & Selama and Kuala Kangsar .